MENELAAH PEMIKIRAN HUMANISME IBNU MISKAWAIH DAN IMPLEMENTASINYA TERHADAP PENDIDIKAN DI INDONESIA - Yulanda, Atika (Universitas Islam Negeri Imam Bonjol Padang, 2021)
AbstractHumanism as a thought in the field of philosophy assesses humans as having a high position compared to other God's creatures. Humans are social creatures who need and adapt to each other. This study describes the Humanism thought of Ibn Miskawaih (330 H/941 AD). He is one of the leading Islamic philosophers whose thoughts are very influential on the thoughts of later figures, especially moral philosophy, so he is often referred to as the father of moral philosophy. This research is a qualitative research using descriptive analysis method. Humanism of Ibn Miskawaih views humans as intelligent beings or creatures who have been awarded by God the potential of reason so that they have the freedom to determine which choices are good and bad. Man lives together and he refuses to live alone or ascetic. Humanism in Ibn Miskawaih's thought is in line with education in Indonesia. To become a perfect human being must be accompanied by good training and education. Education is very important to train the potential that exists in the human person.